Laju Deoksigenasi Sungai Bedadung Hilir Akibat Pencemar Organik - Dharmawan, Agus; Wahyuningsih, Sri; Novita, Elida (Jurnal Teknologi Lingkungan, 2020)
ABSTRACTBedadung stream, located at Rambipuji, Balung, Wuluhan, and Puger, is downstream where dilution of organic wastes occurred and affects its water quality. Microorganisms decompose organic wastes and lead to depletion of dissolved oxygen in the water. The aim of this research was to analyze the deoxygenation rate of Bedadung downstream. The raw data was obtained by measuring stream flows and its water quality parameters (Temperature, DO and BOD) at 5 observed stations. The laboratory analysis consisted of BOD5 and long-term BOD2,4,6,8,10. Increasing the value of BOD for 10 days had a tendency of polynomial pattern order 3 with a coefficient of determination R 0.8987 – 0.9781. The 10 days BOD reactions were used to determine deoxygenation constant K (using least square method) with the result of ranged value 0.043 – 0.372 /day and Ultimate BOD 1.487 – 8.683mg/L. The values of deoxygenation rate at 5 stations were 0.182, 7.997, 7.236, 2.192, and 1.083 mg/L.day. The deoxygenation values were had a similar tendency with the amount of organic waste in the water column and its reduction rate due to the decomposition process.Keywords: Bedadung, BOD, Deoxygenation Rate, DOABSTRAKSungai Bedadung yang terletak di Kecamatan Rambipuji, Balung, Wuluhan dan Puger, merupakan sungai bagian hilir dimana zat pencemar organik bercampur, sehingga mempengaruhi kualitas perairan. Pencemar organik tersebut didekomposisi oleh mikroorganisme perairan sehingga menurunkan DO perairan. Tujuan penelitian ini adalah untuk mengkaji deoksigenasi Sungai Bedadung hilir. Data primer diperoleh dari pegukuran debit dan kualitas air (Temperatur, DO, dan BOD) di 5 (lima) titik pantau. Pengamatan BOD5 dan BOD2,4,6,8,10 dilakukan secara laboratorium. Peluruhan nilai BOD selama 10 hari cenderung memiliki tren polinomial dengan koefisien determinan berada pada nilai 0,8987 – 0,9781. Nilai peluruhan digunakan untuk menentukan nilai K (menggunakan metode least square) dan BOD ultimat. Nilai K di lima titik pantau menunjukkan rentang nilai 0,043 – 0,372 /hari dan BOD ultimat 1,487 – 8,683 mg/L. Sedangkan laju deoksigenasi di lima titik pantau menunjukkan nilai berturut-turut 0,182; 7,997; 7,236; 2,192; dan 1,083 mg/L./hari. Besar nilai deoksigenasi sangat ditentukan oleh banyaknya kandungan pencemar organik dalam air dan kecepatan reaksinya saat proses dekomposisi.Kata Kunci: Bedadung, BOD, Laju Deoksigenasi, DO